2021
DOI: 10.3389/fmolb.2021.645856
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis on Anti-Proliferative and Apoptosis Effects of Curcumin Analog, 1,5-bis(4-Hydroxy-3-Methyoxyphenyl)-1,4-Pentadiene-3-One-Treated Human Glioblastoma and Neuroblastoma Cells

Abstract: Curcumin analogs with excellent biological properties have been synthesized to address and overcome the poor pharmacokinetic profiles of curcumin. This study aims to investigate the cytotoxicity, anti-proliferative, and apoptosis-inducing ability of curcumin analog, MS13 on human glioblastoma U-87 MG, and neuroblastoma SH-SY5Y cells, and to examine the global proteome changes in these cells following treatment. Our current findings showed that MS13 induced potent cytotoxicity and anti-proliferative effects on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 60 publications
1
12
0
Order By: Relevance
“…Besides, MS13 exhibits lower toxicity and highly selective towards PCa cells than normal cells, as indicated by SX values. MS13 showed better cytotoxic activity compared to the parent compound, curcumin against human normal cells, which was consistent with the data described previously (Citalingam et al, 2015;Paulraj et al, 2015;Ismail et al, 2020;Lee et al, 2021). An earlier study reported that FLLL11, which has an identical chemical structure as MS13 was less cytotoxic as curcumin towards human normal cell lines of lung fibroblast (WI-38), bladder smooth muscle and mammary epithelial (non-malignant MCF-10A) (Cen et al, 2009).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Besides, MS13 exhibits lower toxicity and highly selective towards PCa cells than normal cells, as indicated by SX values. MS13 showed better cytotoxic activity compared to the parent compound, curcumin against human normal cells, which was consistent with the data described previously (Citalingam et al, 2015;Paulraj et al, 2015;Ismail et al, 2020;Lee et al, 2021). An earlier study reported that FLLL11, which has an identical chemical structure as MS13 was less cytotoxic as curcumin towards human normal cell lines of lung fibroblast (WI-38), bladder smooth muscle and mammary epithelial (non-malignant MCF-10A) (Cen et al, 2009).…”
Section: Discussionsupporting
confidence: 91%
“…Previously, our group has reported that MS13 (1,5-Bis (4-hydroxy-3-methoxyphenyl)-1,4-pentadien-3-one), a DAP, (Figure 1B demonstrated growth inhibitory effects in time-and dosedependent manner in prostate (Citalingam et al, 2015), cervical (Paulraj et al, 2015), glioblastoma, neuroblastoma (Lee et al, 2021), and colorectal (Ismail et al, 2020) cancer cell lines. Furthermore, MS13 has also shown to be effective than curcumin in inducing apoptosis by modulating apoptosis pathways in gastric (Yoshida et al, 2018), colorectal (Cen et al, 2009) and pancreatic (Friedman et al, 2009) cancer cells.…”
Section: Introductionmentioning
confidence: 90%
“…Notably, those findings are consistent with our findings for the interaction network (Figure 10). Alpha-enolase is not only an adhesive protein, but is also likely involved in other roles concerning glycolysis [6,36]. The results of the protein interaction network are worthy of further study.…”
Section: Discussionmentioning
confidence: 94%
“…Strategies to improve its pharmacokinetic profile could be a perspective of this work. For instance, some studies have shown that structural modifications of polyphenols, such as resveratrol and curcumin, increased their cytotoxic, antiproliferative, and proapoptotic effect [ 47 , 48 ]. Particularly, we have initiated a new project where we synthesize derivatives of CGA that showed a lower IC50 than CGA.…”
Section: Discussionmentioning
confidence: 99%